Kinetic model and parameters study of lignocellulosic biomass oxidative pyrolysis. (15th August 2019) - Ding, Yanming; Huang, Biqing; Wu, Chuanbao; He, Qize; Lu, Kaihua
Abstract: The oxidative pyrolysis of lignocellulosic biomass was investigated based on thermogravimetric experiment compared with the purely non-oxidative pyrolysis. An updated oxidative kinetic model is proposed by importing three oxidative proportion parameters (λ1, λ2, λ3 ) for hemicellulose, cellulose and lignin as the direct extension of previous three-component parallel non-oxidative pyrolysis model. The total of extra 23 oxidative kinetic parameters was obtained by the Shuffled Complex Evolution method and they were applied to further predict the mass distribution of the above three main components. The predicted results proved the oxidative mechanism of biomass: the first stage is caused by the decomposition of hemicellulose and cellulose and partially decomposition of lignin, and the second stage is resulted from both the decomposition of the remaining lignin and char combustion. Highlights: Oxidative pyrolysis of lignocellulosic biomass is studied. Oxidative model is proposed based on the direct extension of non-oxidative one. Extra 23 oxidative pyrolysis kinetic parameters are obtained by SCE. Oxidative pyrolysis mechanism of biomass is verified.